2014
DOI: 10.1002/btpr.1904
|View full text |Cite
|
Sign up to set email alerts
|

Serum‐free spheroid suspension culture maintains mesenchymal stem cell proliferation and differentiation potential

Abstract: There have been many clinical trials recently using ex vivo-expanded human mesenchymal stem cells (MSCs) to treat several indications such as graft-versus-host disease, acute myocardial infarction, Crohn’s disease, and multiple sclerosis. However, the conventional 2-dimensional (2D) culture of MSCs is laborious and limited in scale potential. The large dosage requirement for many of the indications further exacerbates this manufacturing challenge. In contrast, spheroid MSC culture does not require a cell attac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
62
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(64 citation statements)
references
References 70 publications
2
62
0
Order By: Relevance
“…In spheroids derived from tibia bone, CD44, CD73, and CD90 expression is lower, and CD105 expression is much lower, than in monolayer cultures (Frith et al, 2010). CD105 expression in cells derived from human bone marrow MSCs depends on serum content (Alimperti et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In spheroids derived from tibia bone, CD44, CD73, and CD90 expression is lower, and CD105 expression is much lower, than in monolayer cultures (Frith et al, 2010). CD105 expression in cells derived from human bone marrow MSCs depends on serum content (Alimperti et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…It has been demonstrated that MSC spheroids exhibit increased anti inflammation effect, increased differentiation potential, and enhanced expression of cytokines and pluripotent genes. It facilitates the understanding of organogenesis mechanisms and their application in the regenerative medicine (Alimperti et al, 2014;Bogdanova Jatniece et al, 2014;Guo et al, 2014;Murphy et al, 2014;Xiao et al, 2014;Li et al, 2015).…”
Section: Introductionmentioning
confidence: 98%
“…We also evaluated the angiogenic characteristics of thymus MSCs using an established 3D sprouting assay [41][42][43] because 3D culture is known to enhance the regenerative abilities of MSCs and more closely approximates the in vivo setting [44][45][46][47]. In multicellular spheroids, HUVECs and thymus MSCs are in a 3D, highcell-density aggregate during initial formation, facilitating direct contact and paracrine cell interactions.…”
Section: Discussionmentioning
confidence: 99%
“…The use of MSC for tissue repair requires the migration and homing to the site of damaged tissue and it has been shown that both the migratory and proliferation potential of these cells are affected by CDH2 and CDH11 [100, 101]. MSCs have also been shown not only to have differentiation potential but also potent anti-inflammatory effects [102], which are enhanced when cultured as 3D spheroid aggregates [103, 104]. Interestingly, both CDH2 and CDH11 were shown to be critical in the response of synovial fibroblasts to inflammation [105, 106], suggesting that cadherins may also be important in mediating the anti-inflammatory effects of MSC.…”
Section: The Role Of Cdh2 and Cdh11 In Mesenchymal Stem Cell Diffementioning
confidence: 99%